Hybrid endovascular and surgical staged approach for mycotic carotid pseudoaneurysms: a case report and literature review - Marianna, Sallustro; Ilaria, Ficarelli; Teresa, Prisco; Armando, Pontarelli; Giuseppe, Foschini; Marisole, Toni; Valerio, Rinaldi; Priscilla, Nardi; Palumbo, Piergaspare; Giulio, Illuminati; Vito, D’Andrea; Carlo, Ruotolo (Frontiers in Surgery, 2024)
Abstract Background: Mycotic carotid pseudoaneurysms represent a challenge for surgeons. They are uncommon but associated with high mortality and morbidity. Methods: We present a case of a 61-year-old man with a mycotic pseudoaneurysm of carotid bifurcation. The case was managed by a staged approach of open arterial reconstruction using saphenous vein graft, after initial endovascular control using stent graft. We also reviewed the literature available. Results: The patient was discharged to home with patent carotid artery, no sign of infection or bleeding. A CT scan performed 1, 6 months and one year later confirmed the good patency of the graft without imaging of cerebral ischemia. Conclusions: Mycotic pseudoaneurysms of the extracranial carotid artery are rare and should always be surgically treated. This disease, even if rare, request early detection and treatment to avoid fatal outcome. Hybrid staged approach is suggested compared to one-staged surgery in order to avoid rupture ad improve clinical outcome using stent graft associated with antibiotic therapy as bridge treatment until definitive surgery to obtain arterial reconstruction with an autologous graft